Advances in the surgical treatment of Parkinson's disease: systematic review - Fiallos, Guillermina A.; Macías, Valeria D. (Revista Gregoriana de Ciencias de la Salud, 2024)
Parkinson's disease (PD) is seeing an increase in diagnoses. In Ecuador, information on its prevalence is limited, with a study in Manabí reporting 243 cases per 100,000 inhabitants. Characterized by resting tremors, dysarthria, bradykinesia, among other symptoms, treatments include medications such as Levo-dopa, carbidopa, dopamine agonists, and surgical options such as deep brain stimulation. This study aimed to examine the historical evolution of PD therapies and the outcomes of contemporary surgical interventions. A systematic review of articles was conducted from 1994 to 2024, highlighting advances from Aryuvedic texts to the introduction of L-Dopa. Ablative surgeries such as thalamotomies and pallidotomies have demonstrated variable effectiveness, while deep brain stimulation has shown strong evidence of being effective, improving motor symptoms and patients' quality of life. These surgical advances have significantly improved the management of PD, highlighting deep brain stimulation as the most effective and safest method available.